2018
DOI: 10.1128/aac.00074-18
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Metallo-β-Lactamase Inhibitor That Potentiates Meropenem Activity against Carbapenem-Resistant Enterobacteriaceae

Abstract: Infections caused by carbapenem-resistant (CRE) are increasingly prevalent and have become a major worldwide threat to human health. Carbapenem resistance is driven primarily by the acquisition of β-lactamase enzymes, which are able to degrade carbapenem antibiotics (hence termed carbapenemases) and result in high levels of resistance and treatment failure. Clinically relevant carbapenemases include both serine β-lactamases (SBLs; e.g., KPC-2 and OXA-48) and metallo-β-lactamases (MBLs), such as NDM-1. MBL-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Combinations of β-lactams and β-lactam enhancers such as zidebactam (13) and nacubactam (14) have also shown promising activities. Moreover, several MBL inhibitors, including aspergillomarasmine A (15), dipicolinic acid derivatives (16), ANT431 (17), bisthiazolodines (18) and bismuth antimicrobials (19) have been reported. Recently, VNRX-5133 (taniborbactam), a dual SBL and MBL inhibitor have shown potent activity in combination with cefepime against MBL-producers (20).…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of β-lactams and β-lactam enhancers such as zidebactam (13) and nacubactam (14) have also shown promising activities. Moreover, several MBL inhibitors, including aspergillomarasmine A (15), dipicolinic acid derivatives (16), ANT431 (17), bisthiazolodines (18) and bismuth antimicrobials (19) have been reported. Recently, VNRX-5133 (taniborbactam), a dual SBL and MBL inhibitor have shown potent activity in combination with cefepime against MBL-producers (20).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many research groups have developed MBL inhibitors and confirmed their activity against purified MBL enzymes in vitro; however, most inhibitors showed extremely low activity toward live MBL-producing bacteria, suggesting that their permeativity of the bacterial outer membrane is low (7). Thus, only a few MBL inhibitors, such as ME1071, developed by Meiji Seika Pharma (8), and cyclic boronates (9,10), including VNRX-5133 (taniborbactam), developed by Venatorx (11)(12)(13), and ANT431, developed by Antabio SAS (14), are reportedly active against MBL-producing clinical isolates. Nonetheless, none of these compounds have been approved for clinical use.…”
mentioning
confidence: 99%
“…Representative inhibitors of NDM-1 [28][29][30][31][32][33][34][35][36]. ChemMedChem 2019, 14,1271 -1282 www.chemmedchem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim 3, 5, 6,a nd 8 are summarized in Scheme 2.…”
mentioning
confidence: 99%